Disciplinary Liability of legal entities, entities without personality and administrators - Rebollo Puig, Manuel (2016)
The disciplinary liability of legal entities, which the regulation normally accepts, is not an exception to the principles of existing guilty and of personalizing the sanction: it is a liability for action and fault of the legal entity. In particular, it analyzes the liability of legal entities by the actions of their administrators. And, also, it studies the cases in which the Law provides certain complements or qualifications to that liability. Above all, the cases in which the disciplinary liability of the administrators is evident. It also addresses the liability of entities without personality and it highlights the advantages and difficulties that their application entails.